Large‐Scale Synthesis of Strain‐Tunable Semiconducting Antimonene on Copper Oxide. Issue 4 (11th December 2019) - Niu, Tianchao; Meng, Qingling; Zhou, Dechun; Si, Nan; Zhai, Shuwei; Hao, Xiamin; Zhou, Miao; Fuchs, Harald
Abstract: Controlled synthesis of 2D structures on nonmetallic substrate is challenging, yet an attractive approach for the integration of 2D systems into current semiconductor technologies. Herein, the direct synthesis of high‐quality 2D antimony, or antimonene, on dielectric copper oxide substrate by molecular beam epitaxy is reported. Delicate scanning tunneling microscopy imaging on the evolution intermediates reveals a segregation growth process on Cu3 O2 /Cu(111), from ordered dimer chains to packed dot arrays, and finally to monolayer antimonene. First‐principles calculations demonstrate the strain‐modulated band structures in antimonene, which interacts weakly with the oxide surface so that its semiconducting nature is preserved, in perfect agreement with spectroscopic measurements. This work paves the way for large‐scale growth and processing of antimonene for practical implementation. Abstract : High‐quality antimonene with semiconducting nature is fabricated by molecular beam epitaxy on a dielectric oxide substrate. The evolution process and strain‐tunable band structures are revealed by scanning tunneling (ST) microscopy/ST spectroscopy measurements and theoretical calculations. The oxide substrate allows both decoupled electronic properties and direct integration of 2D systems into well‐established fabrication lines, a great advantage for large‐scale synthesis and practical application.